Mechanization starter pack for smallholder farmers: IPSR Innovation Profile - Matin, Md Abdul; Thierfelder, Christian L.; Baudron, Frédéric (2022)
Smallholder agricultural mechanization is the call of the day for Africa. Smallholder mechanization helps to reduce production cost and drudgery making agriculture more attractive to the youth. Successful mechanization in most of the African countries relies on selection, validation, piloting, and scaling of appropriate inexpensive machinery solutions adapted to farm size and financial ability of smallholder farmers. Over the past decade, CIMMYT has tested, validated, and piloted small scale machinery and business models suitable for southern African farmers. Currently there 56 mechanization service providers are operating their businesses in Zimbabwe and Zambia. Based on the experiences and successful piloting, the following starter pack machinery is recommended for scaling through a Service Provider Model. A service provider owns and maintains the starter pack machinery and operate it on a fee-forservice basis benefiting many farmers. The service fee is usually much cheaper for the end users (farmers) compared to the cost of traditional practices and create a win-win situation that makes the business viable for both service providers and farmers.